ESTIMASI HILANGNYA CADANGAN KARBON DARI PERUBAHAN PENGGUNAAN LAHAN DI KABUPATEN BOGOR - Gatot Setiawan; Lailan Syaufina; Nining Puspaningsih (Graduate School Bogor Agricultural University (SPs IPB), 2015)
One of the primary sectors that contributes to green house gas emissions is land use changes. Bogor Regency is one of the districts close to the capital city and industrial areas so that the intensity of land use changes are very dynamic. This study aims to determine the dynamics of land use changes and CO2-eq emissions from land use change in 2000 to 2014 in Bogor. In the period 2000-2014 the most land undergone many changes occur in mixed garden, cropland, open land and shrub that converted turned into settlement with a total amounted to 11.12% of the total area, while the CO2-eq emissions in 2005-2009 increased approximately six times the emissions from 2000-2005 in the amount of 681 006.94 tons of CO2-eq per year.Keywords: green house gas emission, land use change, CO2-eq emissions